Penggunaan Tindak Tutur Asertif Dokter dalam Komunikasi Medis - Basri, Muh. Bahly (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2020)
Research purpose to: (1) describe the form of assertive speech acts of doctors in medical communication; (2) describe the function of physician’s assertive speech acts in medical communication. This research is qualitative research. This research was conducted at the RSUD Haji Makassar. The research design used is descriptive qualitative. The focus of this study, namely data in the form of words, phrases, clauses, and assertive sentences put forward by doctors when communicating with patients. Sources of research data, namely doctors who have specialized. Data collection techniques are done through observation and recording. The research instrument consisted of the main instruments namely researchers and supporting instruments including data analysis guides, observation guides, and recording devices. The results of the study revealed that assertive speech acts used by doctors, namely declarative assertive speech acts, interrogative speech assertive speech acts, and imperative speech assertivespeech acts. Declarative speech consists of declarative meaningful explanations of circumstances, advice, estimates, disagreements, and affirmations. Interrogative speech consists of interrogative meaningful states, tells, suggest, complains, and demands. The imperative speech consists of imperative meaningful insistence and suggestion. The assertive speech acts function used by doctors, namely the stated function, the function of notifying, the function of suggesting, the function of complaining, and the function of demanding. The use of various forms of assertive speech act doctors are represented so that patients get treatment and healing. The use of a variety of assertive speech act functions is represented by doctors in order to provide information and help patients to get healing.